In Vitro Antimicrobial Studies on the Saponin Obtained From Cesalpinia sappan Linn. - N. Yadava, R. (Asian Journal of Chemistry, 2010)
In the present work, the antimicrobial activity of the saponin obtained from Caesalpinia Sappan Linn. has been discussed.